Antigenic relationship between the common antigen (OEP) of Pseudomonas aeruginosa and Vibrio cholerae. - Hirao, Y (1978)
Antibodies were found by the OEP-passive hemagglutination test to cross-react with the common antigen (OEP) of Pseudomonas aeruginosa in sera of rabbits immunized with two serotype (Inaba and Ogawa) strains of Vibrio cholerae. The titer in the OEP-passive hemagglutination reaction rose later than did the agglutinin titer and reached a peak of 640 to 1,280. The titers of OEP antibody formation in rabbits immunized with V. cholerae were almost the same as that of P. aeruginosa. The common antigen of P. aeruginosa was confirmed to exist serologically in both strains of V. cholerae as determined by the indirect fluorescent antibody test and the agar gel precipitin test. Passive immunization with the V. cholerae immune rabbit serum significantly protected mice against P. aeruginosa infection. Purified antibodies cross-reacting with the OEP of P. aeruginosa derived from the V. cholerae immune rabbit sera by OEP-coupled affinity chromatography protected mice against P. aeruginosa infection as compared with the control group, which was injected with 100 microgram of immunoglobin G not containing OEP antibody. The purified antibodies (2.5 microgram per mouse) protected animals challenged with approximately 10,000 50% lethal doses in the control group. Consequently, the common antigen (OEP) of P. aeruginosa proved to be a common antigen of V. cholerae both serologically and in possessing infection protective properties.